STUDI META-ANALISIS KONDISI HUTAN MANGROVE TERHADAP KEANEKARAGAMAN HEWAN DI PULAU RAMBUT, KEPULAUAN SERIBU, DKI JAKARTA - Dinda Nasifah Caesaria; Nisa Akmadina; Sheilla Safitri; Tiara Cahyaningtyas; Wanda Khairina; Ratna Dewi Wulaningsih; Erna Heryanti (Universitas Islam Negeri Sumatera Utara, 2021)
Mangrove forest is a form of a transitional ecosystem from land and sea so it has many roles and functions for the ecosystem, one of which is maintaining the biological stability of the waters. This study aims to determine the condition of the mangrove forest and its effect on the diversity of animal species found on Rambut Island. The method used in this study is a meta-analysis by combining some previous data through a literature study on the condition of mangrove forests and animal diversity on Rambut Island. The study results show that on Rambut Island 18 species of mangrove plants have been identified and in the last 10 years, there has been a decrease in the number of mangrove species to 6 species in 2021. The mangrove forest is dominated by Rhizophora mucronata species. Animal species found in mangrove forests are dominated by groups of water birds, such as the great egret (Egretta alba). The decrease in the number of mangrove plant species resulted in a decrease in the abundance and diversity of animal species on Rambut Island. This is because these animals lose mangrove vegetation which provides a place to find food and protection for the animals that live in them. Therefore, the mangrove forest is an area that must be preserved so that it can benefit the animals that live in it.